A needs analysis of English for business students at a private university in Malaysia / Daksayani Ganeson - Daksayani , Ganeson (2018)
Given that the principal language of communication in the business field is English, this study looks into the English language needs and problems faced by business students at a private university in Shah Alam, Malaysia. The main aim of this study is to identify a) the English Language problems of the business students, b) the English Language needs and c) the language skills required in a proposed English Language syllabus for the business students. As this is a qualitative study, multiple sources of data were collected via semi-structured interviews with one Academic head, three Business lecturers and three Industrial supervisors and questionnaires administered to eighty business students. The findings of the study revealed that business students faced major problems in a) speaking- poor grammar, incorrect pronunciation, and giving presentation, b) writing- writing various business documents, c) listening- understanding clients’ and superior’s pronunciations, and d) reading – understanding business terminologies and general vocabulary. In terms of their needs, all of the business students wanted to improve their English and were interested in enrolling in the Business English course. The needs of the business students were, to focus on the four major skills, grammar and vocabulary. Some of the recommendations for the proposed English for Business syllabus given by the respondents of this study were a) speaking – effective communication at the workplace, negotiating in various situations, making polite conversations with prospective clients and telephoning skills, b) writing- techniques of writing business documents, techniques of writing negative messages and editing business documents, c) listening- watching YouTube videos to understand different accents and pronunciations, and d) reading – skimming and scanning business documents, interpreting non-linear texts and reading business related articles. Based on the findings, a three hour, 14 week Business English syllabus was developed.